Experimental rat model for brain death induction and kidney transplantation - Esmaeilzadeh, Majid; Sadeghi, Mahmoud; Heissler, Hans E.; Galmbacher, Roland; Majlesara, Ali; Al-Afif, Shadi; Mehrabi, Arianeb (Journal of investigative surgery, 2020)
Background: Experimental animal research has been pivotal in developing clinical kidney transplantation (KTx). One donor-associated risk factor with negative affect of transplantation outcome is brain death (BD). Many rat models for BD and KTx have been developed in the last decade, but no surgical guidelines have been developed for these models. Here, we describe a surgical technique for BD induction and the cuff technique for experimental KTx in rats.Methods: After intubation and mechanically ventilation of sixteen healthy adult male Sprague-Dawley rats were induction of BD performed. Animals were kept hemodynamically stable for eight hours. Then, the kidney was prepared and perfused with standard histidine-tryptophan-ketoglutarate solution. After explantation, grafts were immediately implanted in recipients using the cuff technique and reperfused. After 2 h of observation, animals were sacrificed by intravenous administration of potassium chloride.Results: In the early phase of BD, heart rate increased and mean arterial pressure decreased. Partial variations were observed in O2 partial pressure, O2 saturation, and HCO3. During the 2-h observation phase, all transplanted kidneys were sufficiently perfused macroscopically. There was no hyperacute rejection.Conclusions: It is feasible to observe BD for 8 h with maintained circulation in small experimental settings. The cuff technique for KTx is simple, the complication rate is low, and the warm ischemia time is short, therefore, this could be a suitable technique for KTx in the rat model.
Published online: 18 Oct 2018
Gesehen am 01.04.2020